Selectivity among educational migrants? A multi-sited investigation - Héctor Cebolla-Boado; Yasemin Nuhoglu Soysal (Chinese Sociological Review, 2023)
Research on migration is shifting from comparisons between migrants and non-migrants in destination countries to a multi-sited origin-destination perspective, which allows us to address the issue of migrant selectivity. Selectivity implies that migration results from a systematic bias according to which emigrants differ from non-migrants in origin. The literature on selectivity has overlooked educational migrants, an important contributor to the flow of highly skilled international migration. We investigate whether international students in tertiary education replicate the pattern of positive selection that is systematically found among the general migrant population. Our paper compares leavers and stayers using social background and selected individuality traits to study this phenomenon. Using the first large-scale representative survey of Chinese students enrolled in tertiary education in China, Germany, and the UK, we provide two critical findings. Firstly, we find a pattern of hyper-selection by social background among Chinese students abroad compared with stayers at home, although international education is a more democratic phenomenon than is generally believed. Secondly, we find that selection in terms of "unobservable" individuality traits is rather modest.
Keywords: 300